Lynley [season 1] [videorecording (DVD)] - Englishby, Paul (BBC, 2025)
Two mismatched detectives from different worlds create a unique duo in this fresh adaptation of Elizabeth George's murder mysteries. Tommy Lynley is a brilliant police detective but an outsider in the force simply by virtue of his aristocratic upbringing. He is paired with Barbara Havers, a sergeant with a maverick attitude and a working-class background. With seemingly nothing in common and against all odds, the mismatched duo of Lynley and Havers become a formidable team, bonded by their desire to see justice done. His brain and her spirit, his knowledge and her instincts. Only by working side by side will they find where they truly belong.